Genetic evaluation of farmer's rice varieties for physiological and yield attributing responses exploiting principal component analysis - Khoth, Nivesh; Singh, Sanjay; Ramakrishnan, R Shiv; Koutu, G K; Sharma, Radheshyam; Kumar, Ashish; Pathak, Nidhi; Kumawat, Pradeep; AJ, Akarsha; ., Abhiraj; Dwivedi, S K (ORYZA-An International Journal of Rice, 2021)
An experiment was conducted on 30 farmer’s rice varieties collected from different districts of Madhya Pradesh to identify the genetic components contributing to phenophasic development, physiological, yield attributes and biochemicaltraits. Principal component analysis was performed to rank the farmer's varieties based on PC scores acquired as per the trait studied. Out of twenty-six traits, only five principal components (PCs) exhibited more than 1.00 Eigen value and showed 85.80% of total cumulative variability. The PC1 showed 58.55%, while PC 2, PC 3, PC 4 and PC 5, exhibited 10.29%, 7.03%, 5.23% and 4.69% variability, respectively. The PC 1 reported the highest variability, which was associated with physiological and yield related traits. The PC 2 was dominated by biochemical traits, while PC3 was mostly dominated for yield traits. The PC 4 was dominated by physiological traits, and PC5 for phenological and yield-related traits. Farmer's variety Pandu was superior for Chlorophyll content index (38.27), total dry matter production (38.15 g plant-1), Leaf area index (4.09), Leaf area duration (17982 cm2 days) and crop growth rate (0.00282 g m-2 day-1).PCA revealed that genotype Pandu (7.224) acquired highest PC scorefollowed by Raibua (5.364), Bahurupi (5.103) and Chinnor 1 (4.750) respectively. Farmers varieties Pandu, Chhindikapoor, Bahurupi, Sitha Chandan, Chinnor 2, Chinnor 1 and ChhotaSathiya were contributed their presence in maximum PCs of this investigation. The identified lines will be utilized in the rice breeding programme to develop improved rice varieties for high yield and maximum physiological efficiency.